PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 - 2019 - Abdul Salam; Viqih Oschar Sahuddin; Hanifa Sri Nuryani (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2022)
This research aims to analyze the Effect of Financial Performance on research Stock Returns on Manufacturing Companies Listed on the Indonesia Stock Exchange in 2014-2019. This uses quantitative methods. in this study are manufacturing companies listed on the Indonesia Stock Exchange. Data was obtained using Multiple Linear Regression analysis techniques through SPSS 16 software. The results of this study showed that (1) Earning Per Share has no effect and is not significant to Return Stock. (2) Return on Investment significantly influences the Return Stock. (3) Return on Equity significantly influences the Return on Stock.